(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article discusses the concepts of «identity» and «selfpresentation». The problem of identity formation in adolescence is analyzed. The dependence of self-presentation on the state of identity is established. Listed are the features of communication on the Internet. Computer nicknames are considered as a way of self-presentation on the Internet. The results of a study of self-presentation of young men using computer nicknames are presented. Computer nicknames are systematized and analyzed. The dependence of the choice of a computer nickname on the state of identity in young people is established. The role of a computer nickname in the formation of identity is determined.